Waxes composition of Quercus suber reproduction cork from different Spanish provenances - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (Wood Science and Technology, 1999)
The chemical composition of waxes was studied in Quercus suber cork planks collected in seven localities of the three main production areas of Spain. Waxes were extracted with chloroform (CHCl3 ) and the extract was submitted to saponi®cation in order to obtain the neutral and acid fractions. The trimethylsilyl derivatives of both fractions were analysed by GC-MS. The seven populations cannot be distinguished by their total contents of waxes (Chloroform extract) and of the neutral and acid fraction. This lack of differences could be due to the important variability among samples of each population. The neutral fraction was mainly composed of fatty alcohols (all the even members from C18 to C26 , with traces of the intermediate odd members and some unsaturated groups) and triterpenes (11 components, among them friedelin, betulin and cerin were identi®ed) and a very small amount of monocarboxylic fatty acids (C16 and C24 members) was also present. The main group of compo- nents of the acid fraction was that of fatty acids (saturated even C14±C24 and odd C15 , C17 , C21 members, accompanied by a great amount of unsaturated terms and some x-hydroxyacids, 18-hydroxy-9,12-octadecadienoic and 18-hydroxy-9-oct- adecenoic acids). Four triterpenes and the C20 and C24 alcohols were also detected in the acid fraction. Signi®cant differences were found among the corks of the various provenances in the global contents of alcohols and triterpenes and in these individual components contents of the neutral fraction. Concerning the differences among the various provenances in the contents of the groups of fatty acids, alcohols, and triterpenes in the acid fraction, a higher number of differ- ences were obtained in the comparisons of the contents of acids and triterpenes, whereas the differences were practically null in the case of the alcohols. When the differences were studied considering the individual compounds, the relation with the behaviour of the contents of the groups of components was not as clear as it happens in the neutral fraction. In this case, the differences were scarcer and they did not show a unique pattern, neither in the components, nor the populations. There is no correspondence in the differences among the provenances regarding the components of the neutral fraction or those of the acid fraction. No clear relationship was found between the geographical proximity of the provenances and chemical similarity of the waxes composition.
Keywords: Acid fraction; component (voyant); Cork; neutral fraction; provenance; waxes

Waxes composition of reproduction cork from Quercus suber and its variability throughout the industrial processing - Conde, E.; GARCIA-VALLEJO, M. C.; Cadahia, E. (Wood Science and Technology, 1999)
The chemical composition of waxes was studied in cork planks from three different trees of Spanish Quercus suber at four different stages of the in- dustrial processing of the ®rst transformation: stripping, ®rst rest, boiling fol- lowed by open air rest and boiling followed by store-room rest. Waxes were extracted with chloroform (CHCl3 ) and the extract was submitted to saponi®cation in order to obtain the neutral and acid fractions. The trimethylsilyl derivatives of both fractions were analysed by GC-MS. An important decrease of the total content of waxes -CHCl3 extract-(average values: 10.13 to 4.91%) and of the acid fraction (average values: 2.51 to 0.96%) was observed throughout the industrial processing. Some differences were also found among trees, two of them being richer in total waxes (average, 8.14 and 7.71%) than the other one (average, 4.67%). Concerning the three groups of identi®ed components (fatty acids, fatty alcohols and triterpenes), the contents of the fatty alcohols and acids suffer an important reduction during the ®rst rest (average values: 30.39 to 17.53% and 58.73 to 31.48%, respectively), while after boiling, there is a decrease of the triterpenes concentrations (79.16 to 58.00% -neutral fraction- and 40.23 to 23.20% -acid fraction-), being greater when the second rest is carried out in a store room. Signi®cant differences among trees were only found in the fatty alcohols contents. The neutral fraction was mainly composed by fatty alcohols (all the even members from C18 to C26 , with traces of intermediate odd members and some unsaturated groups, C20 and C21 ) and triterpenes (14 components, among them friedelin, betulin and cerin were identi®ed), and a very small amount of monocarboxylic fatty acids (C16 , C18 , C22 and C24 members) was also present. The main group of components of the acid fraction was that of fatty acids (saturated even C12±C24 and odd C15 , C17 , C21 members, accompanied by a great amount of unsaturated terms and some x-hydroxyacids, 18-hydroxy-9,12-octadecadienoic and 18-hydroxy-9-octadecenoic acids). Four triterpenes, the C20 , C24 and C28 alcohols and ferulic acid were also detected in the acid fraction. Some of these individual components of each fraction were also affected by the industrial processing and presented signi®cant differences among the studied trees.
Keywords: Acid fraction; component (voyant); Cork; indutrial processing stage; neutral fraction; waxes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
Keywords: stomata; taxonomy; Trichomes; waxes

European and Mediterranean oaks (Quercus L.; Fagaceae): SEM characterization of the micromorphology of the abaxial leaf surface - Bussotti, Filippo; Grossoni, Paolo (Botanical Journal of the Linnean Society, 1997)
This paper examines micromorphological characteristics (trichomes, waxes, stomata) of the abaxial leaf surface of European and Mediterranean oaks. Observations were performed In-scanning electron microscopy, and the purpose of the investigation was to ascertain whether it is possible to distinguish the different species taxonomically using these features. Several species, as well as some subspecific entities and taxa considered doubtful, were taken into consideration. Subgenera appear to be well-defined: e.g. the subgenus Quercus is characterized by waxes arranged in vertical scales, the subgenera Cenis and Sclerophyllodris by smooth waxes. They differ because the former has markedly elliptical stomata, while the latter two have roundish stomata. The different species are also fairly easy to distinguish, and this fact confirms the taxonomical validity of the parameters we have taken into consideration. In some cases subspecific entities and doublful species do not diflcr at all from the related species, but in others they present such marked variations that it is difficult even to classify them with certainty. The most critical taxonomic groups (i.e. those which include a number of specific and subspecific entities often too difficult to distinguish from each other) are the series Quercus robur – Quercus petraea,– Quercus pubescens and the Quercus faginea,– Quercus Insitanica Quercus canariensis group.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: stomata; taxonomy; Trichomes; waxes